The Retrospective Analysis of Introduction of Inclusive Education in Germany - Давиденко, Ганна (Pedagogy of Higher and Secondary Education, 2015)
Davydenko H. V. The Retrospective Analysis of Introduction of Inclusive Education in Germany. The article deals with the process of implementation of inclusive education in Germany. The historical landmarks of inclusive education formation in Germany are studied. The legislative background and modern state of inclusive education implementation for people with disability are outlined.